Sistem Informasi Manajemen UKM dan ORMAWA di Polman Negeri Babel - Azzah Haaniyah, Adinda; Afriansyah, Riki; Agita Rindri, Yang (Jurnal Inovasi Teknologi Terapan, 2023)
Student affairs at Polman Negeri Babel are divided into Student Activity Units (UKM) and Student Organizations (ORMAWA). Administrative processes such as submitting work programs, accountability reports, and submitting activity proposals are not well structured. There is no data collection for UKM and ORMAWA members, the membership registration process is still conventional and there is a lack of information delivery media. Based on these problems, research was carried out which aimed to build a Management Information System for UKM and ORMAWA at Polman Negeri Babel. The methods used in data collection are observation and interviews. As for the research method used prototype method. The method used to test the system is the User Acceptance Test (UAT) method with black box testing and beta testing techniques. The system built is in accordance with the plan based on the results of black box testing. While the beta testing results obtained a percentage of 88.48%. It can be concluded from this study that the development of the Management Information System for UKM and ORMAWA at Polman Negeri Babel suits user needs and facilitates the administrative process, membership registration, conveying or obtaining information, records logs of activities and membership of UKM and ORMAWA